FORMULASI DAN KARAKTERISTIK BEDAK DINGIN KOMBINASI BEBERAPA PATI - Raymond Arief (Akademi Farmasi Yamasi Makassar, 2022)
Cold powder is one of the traditional cosmetics made from natural ingredients, processed traditionally and based on knowledge for generations. This study aims to formulate cold powder using the basic ingredients of a combination of rice starch that has been soaked for one day (F1) and for five days (F2). added starch of yam bean, curcuma and mung bean and conducted quality test preparations produced with test parameters including: organoleptic, homogenous, pH value and spread test. The results showed that F1 and F2 preparations showed uniform results and found the provisions set.